1997
DOI: 10.1149/1.1837812
|View full text |Cite|
|
Sign up to set email alerts
|

Spectroelectrochemical Study of the Role Played by Carbon Functionality in Fuel Cell Electrodes

Abstract: X-ray absorption spectroscopy was used to identify specific types of nitrogen and sulfur-based carbon functionality present in the carbon black supports of fuel cell anodes and cathodes. The effects of these functional groups on the electrocatalytic performance of small platinum particles, dispersed on the carbon, during methanol oxidation and oxygen reduction were assessed. Electrodes functionalized with nitrogen had enhanced catalytic activities toward oxygen reduction and methanol oxidation relative to untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 1 publication
1
63
0
1
Order By: Relevance
“…), respectively [29]. The quinonoid imine (=N-) signal with BE of 398.8 eV was a solid evidence proving the presence of Pt-N bond [6], which facilitated the methanol electro-oxidation by reducing electron density on Pt [30,31].…”
Section: Xps Of As-prepared Catalystsmentioning
confidence: 89%
“…), respectively [29]. The quinonoid imine (=N-) signal with BE of 398.8 eV was a solid evidence proving the presence of Pt-N bond [6], which facilitated the methanol electro-oxidation by reducing electron density on Pt [30,31].…”
Section: Xps Of As-prepared Catalystsmentioning
confidence: 89%
“…Nitrogen-doping into carbon can be performed either directly during synthesis or by post-synthetic treatment. However, post-treatment of carbon materials often yields just surface functionalization, [76][77][78][79] and thus does not change the bulk material properties. In contrast, doping of carbons during solid synthesis by using nitrogen containing precursors can yield a homogeneous incorporation of nitrogen into the entire carbon material.…”
Section: Nitrogen-doped Carbons In Metal-free Catalysismentioning
confidence: 99%
“…This can be accomplished, in part, by controlling the Pt adsorption sites on the catalyst support. It has been shown recently that by doping the carbon support with N-containing molecules, it is possible to provide a high density of active sites on the catalyst support, which ultimately leads to a high density of small Pt particles on the support and high catalytic activity with a much smaller amount of Pt [3,4]. Several studies have shown that N-doping increases the catalytic activity of carbon nanostructures [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown recently that by doping the carbon support with N-containing molecules, it is possible to provide a high density of active sites on the catalyst support, which ultimately leads to a high density of small Pt particles on the support and high catalytic activity with a much smaller amount of Pt [3,4]. Several studies have shown that N-doping increases the catalytic activity of carbon nanostructures [4][5][6]. Theoretical calculations involving N-doping of carbon nanotubes (CNTs) suggest that pyrrolic and pyridinic N atoms decrease the band gap of the graphite lattice [7].…”
Section: Introductionmentioning
confidence: 99%